The Effect of Interleukin-10 And Its Relationship with The Level of White Blood Cells in Women Spontaneous Miscarriage Undergoing Intracytoplasmic Sperm Injection (ICSI) technique - Dhirgam F. Hassan Al-Shimerty1 ; Alaauldeen S. M. AL-Sallami2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was conducted on 84 samples of women subject to the ICSI program . Blood sample was taken tomeasure WBC count , Interleukin-10 and ?-hCG levels . Groups were divided based on the ?-hCG level totwo groups (Pregnant Women Group - Pregnancy Failure Group) and the total of pregnant women dividedinto (Pregnancy Group and spontaneous miscarriage) .The results of the current research showed a significant increase in the level ?-hCG and that the increasein the level of this hormone is evidence of the presence of high success rates for pregnancy in women whoperformed operations IVF, where the success rate at the beginning of the matter reached 61.9%, after whichit decreased to 33.3% after the first three months due to the occurrence of spontaneous miscarriage ofpregnant women due to various immunological and physiological reasons, as well as a positive correlationbetween the level of ?-hCG and other parameters within the study (Interleukin-10 -WBC).The results of the current research also showed a significant difference between the group (pregnancyfailure) and the group (spontaneous miscarriage) compared with the control group (continued pregnancy)in relation to the level of Interleukin-10, Also, The results of the current research showed a significantdifference between the group (pregnancy failure) and the group (spontaneous miscarriage) compared withthe control group (continuation of pregnancy) in relation to the level of WBC, and the present study found apositive relationship between the level of Interleukin-10 and WBC